Distinct Morphological, Physiological, and Biochemical Responses to Light Quality in Barley Leaves and Roots - Klem, Karel; Gargallo-Garriga, Albert; Rattanapichai, Wutthida; Oravec, Michal; Holub, Petr; Veselá, Barbora; Sardans, Jordi; Peñuelas, Josep; Urban, Otmar (Frontiers in Plant Science, 2019)
Light quality modulates plant growth, development, physiology and metabolism through a series of photoreceptors perceiving light signal, and related signaling pathways. Although the partial mechanisms of the responses to light quality are well understood, how plants orchestrate these impacts on the levels of above and below-ground tissues and molecular, physiological and morphological processes remain unclear. However, the re-allocation of plant resources can substantially adjust plant tolerance to stress conditions such as reduced water availability. In this study, we investigated in two spring barley genotypes the effect of UV-A, blue, red and far-red light on morphological, physiological and metabolic responses in leaves and roots. The plants were grown in growth units where the root system develops on black filter paper, placed in the growth chambers. While the growth of aboveground biomass and photosynthetic performance were enhanced mainly by the combined action of red, blue, far-red and UV-A light, the root growth was stimulated particularly by supplementary far-red light to red light. Exposure of plants to full light spectrum also stimulates the accumulation of numerous compounds related to stress tolerance such as proline, secondary metabolites with antioxidative functions or jasmonic acid. On the other hand, full light spectrum reduces the accumulation of abscisic acid which is closely associated with stress responses. Addition of blue light induced accumulation of GABA, sorgolactone or several secondary metabolites. Because these compounds play important roles as osmolytes, antioxidants, UV screening compounds or growth regulators, the importance of light quality in stress tolerance is unequivocal.